2020
DOI: 10.3390/su122310000
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Mitigation Strategies to Improve Pedestrian Thermal Comfort in Urban Environments: A Review

Abstract: Thermal comfort is one of the main factors affecting pedestrian health, and improving thermal comfort enhances walkability. In this paper, the impact of various strategies on thermal-comfort improvement for pedestrians is thoroughly evaluated and compared. Review studies cover both fieldwork and simulation results. These strategies consist of shading (trees, buildings), the orientation and geometry of urban forms, vegetation, solar-reflective materials, and water bodies, which were investigated as the most eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 152 publications
(182 reference statements)
2
25
0
1
Order By: Relevance
“…In many research studies, ENVI-met has proven its success in performing thermal simulations for outdoor areas. (M. Fahmy, Mahmoud, Elwy, & Mahmoud, 2020;Gehl Jan, 1996;Yang et al, 2011;Yilmaz, Mutlu, & Yilmaz, 2018;Nasrollahi, Ghosouri, Khodakarami, & Taleghani, 2020).These studies confirmed an agreement between the measured data (from the field measurements or observed data at the local meteorological stations) and simulated air temperatures. Envi-met has the capability to simulate the microclimate of any location all over the world.…”
Section: Envi-met Validation and Limaitationsupporting
confidence: 66%
See 1 more Smart Citation
“…In many research studies, ENVI-met has proven its success in performing thermal simulations for outdoor areas. (M. Fahmy, Mahmoud, Elwy, & Mahmoud, 2020;Gehl Jan, 1996;Yang et al, 2011;Yilmaz, Mutlu, & Yilmaz, 2018;Nasrollahi, Ghosouri, Khodakarami, & Taleghani, 2020).These studies confirmed an agreement between the measured data (from the field measurements or observed data at the local meteorological stations) and simulated air temperatures. Envi-met has the capability to simulate the microclimate of any location all over the world.…”
Section: Envi-met Validation and Limaitationsupporting
confidence: 66%
“…Therfore, water bodies are inputted as a type of soil, and the process is limited to the transmission and absorption of the shortwave radiations. (Nasrollahi et al, 2020)…”
Section: Envi-met Validation and Limaitationmentioning
confidence: 99%
“…Urban vegetation can make a significant contribution to climate change adaptation and mitigation strategies by cooling cities through shading and evapotranspiration, by mitigating the effects of wind speed and turbulence helping enhance pedestrian comfort, by slowing and filtering the runoff from rain events, contributing to improve water quality, and to reduce storm water runoff, flooding, and waterway pollutants and by filtering atmospheric pollutants include nitrogen dioxide and sulphur dioxide, and larger particulate matter [6][7][8][9][10][11]. However, the potential of these effects depends on the phytosanitary and biological status of the vegetation.…”
Section: Climate Change and Urban Vegetationmentioning
confidence: 99%
“…It is important to consider that vegetation in the urban environment is stressed by anthropic and natural factors exacerbated by climate change. Specifically, climate change influences plants at all stages of development: germination, growth, and reproduction [9]. Temperature and water availability affect the timing and success of seed germination and disrupt pollen development and fertilization [12] and reduce its viability [13], and directly affect photosynthesis and growth rates; in particular, drought reduces growth by inducing stomatal closure and decreasing photosynthetic capacity [14].…”
Section: Climate Change and Urban Vegetationmentioning
confidence: 99%
“…Various other studies have attempted to quantify the respective contribution of each of the processes involved in the cooling effect, which combines a radiative component and an evaporative component, i.e., shading and transpiration [7,45]. Various studies used either field measurements (e.g., [46][47][48][49]) or model simulations (e.g., [50][51][52]). Nevertheless, more effort is needed to improve our understanding of the effects that landscaping and land management has on leaf area and transpiratory cooling of trees.…”
Section: Effect Of Tree Management Practices On Cooling Potentialmentioning
confidence: 99%